2019
DOI: 10.1002/tie.22092
|View full text |Cite
|
Sign up to set email alerts
|

Establishment mode choice by Chinese firms in Latin America: The role of host country‐specific experience and government official visits

Abstract: This study addresses establishment mode decisions by emerging-market multinational enterprises entering other emerging economies. More precisely, we examine the influence of prior host country experience and home government official visits on the choice between the acquisition of a local company and the creation of a new subsidiary from scratch. By analyzing 315 investments carried out by Chinese firms in Latin America, we obtain that they are more likely to enter through an acquisition when they have establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…International business scholars have previously utilized such data to examine FDI location choices (e.g.,Albino-Pimentel, Dussauge, & Shaver, 2018;Filippaios, Annan-Diab, Hermidas, & Theodoraki, 2019).Prior research has also shown that various institutional factors in the host country can affect the choice of establishment modes of Chinese MNEs. For example,Quer, Rienda, and Andreu (2020) report that Chinese firms are more likely to enter Latin American markets through acquisitions when they have prior experience operating in the host country. Similarly,Alon, Elia, and Li (2020) suggest that Chinese MNEs are more likely to use M&As when there are more previous investments in the same host markets.…”
mentioning
confidence: 99%
“…International business scholars have previously utilized such data to examine FDI location choices (e.g.,Albino-Pimentel, Dussauge, & Shaver, 2018;Filippaios, Annan-Diab, Hermidas, & Theodoraki, 2019).Prior research has also shown that various institutional factors in the host country can affect the choice of establishment modes of Chinese MNEs. For example,Quer, Rienda, and Andreu (2020) report that Chinese firms are more likely to enter Latin American markets through acquisitions when they have prior experience operating in the host country. Similarly,Alon, Elia, and Li (2020) suggest that Chinese MNEs are more likely to use M&As when there are more previous investments in the same host markets.…”
mentioning
confidence: 99%
“…This is a dummy variable that takes the value of (1) if the firm acquired a local company and the value of (0) if it made a greenfield investment (Barkema and Vermeulen, 1998; Meyer et al ., 2014; Sun et al ., 2021b). The latter category also includes greenfield joint ventures (Brouthers and Hennart, 2007), as this has been the criterion used in some prior studies on establishment mode choice (Barkema and Vermeulen, 1998; Quer et al ., 2020a, b).…”
Section: Methodsmentioning
confidence: 99%
“…Within this context, diplomatic relationships between countries play a significant role. They symbolize an interaction between the institutions of origin and destination, that acts as a “bridge” between countries and can be a substitute for firm's experience (Duanmu, 2014; Li et al ., 2018; Quer et al ., 2020a; Shapiro et al ., 2018).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…At first, China's outward FDI stock in transport was selected as the output indicator by country and region. Secondly, based on the existing literature[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], we selected 5 first-level indicators and 14 second-level indicators. e first-level indicators were, respectively, political environment, economic environment, institutional environment, humanistic environment, and social environment.…”
mentioning
confidence: 99%